“If it’s really excessive, it can enter your heart”: A Mixed Methods Investigation of Bullying Among Early Adolescents in Semarang, Indonesia - Fine, Shoshanna L. (Journal of interpersonal violence, 2023)
Bullying is a major public health concern for Indonesian adolescents, with well-documented links to a range of emotional and behavioral problems. Despite such evidence, few investigations have employed qualitative methods to illuminate youth’s own perceptions of bullying and its psychosocial correlates in this context. The current study aimed to address this gap through an exploration of Indonesian adolescents’ motivations, perceptions, and beliefs regarding bullying. Building on prior quantitative findings, an explanatory sequential mixed methods approach was used to better understand the myriad ways in which bullying ties into other psychosocial challenges. Qualitative interviews were conducted with a total of 45 adolescents ages 13 to 14 (25 girls and 20 boys) in two junior high schools in Semarang between October and December 2019. Interviews were audio-recorded, transcribed verbatim, and translated into English for analysis. Qualitative data were then coded using an inductive thematic analysis approach. Interviews yielded contextual insights into adolescents’ definitions of bullying including the distinction between “normal” and “serious” bullying; related risk behaviors; key drivers; social and emotional consequences; and coping strategies. Across these thematic categories, a number of noteworthy gender differences emerged, highlighting the role that underlying gender norms can play in driving bullying involvement. Further, findings emphasize the need to develop a locally valid definition of bullying which takes into account the ways in which emotional distress may be both a criterion and a consequence of bullying. Findings can be used to inform bullying prevention programs targeting Indonesian youth.